Phytochemical properties of biobased oils and their application for maintenance of citrus fruits quality - Adams, Abdul-Rahaman; Irtwange, Simon V; Aloho, Kortse P; Barau, Bashir (Journal of Postharvest Technology, 2022)
Postharvest losses in citrus are often associated with excessive loss of moisture, poor cooling, and temperature abuse during harvest through to consumption. The incidence of decay from microorganisms can determine the quality of citrus and reduce the shelf life. At present there are consumer concerns regarding some pathogen’s resistance to fungicides from synthetic sources. The cost involved in the application of fungicides makes it unprofitable for small scale producers and the retail sectors. An alternative preservative that can offer effective maintenance of citrus fruit quality during storage is needed. Therefore, this review summarises the functional properties of biobased oils and their application in the control of moisture loss, firmness, Total soluble solid, titratable acidity, pH, ascorbic acid and sensory properties of citrus fruits. It was established that there are some positive thrives on quality maintenance of citrus but antifungal activity of individual compounds in oils still require further research. Also several oils from seeds have been reported whilst biobased oils from plant leaves not extensively exploited. This review provides insight on beneficial effects of biobased oils on quality and shelf life of citrus fruits.